Implementasi Peraturan Bupati Nomor 17 Tahun 2021 Tentang Sekolah Ramah Anak di Kabupaten Sukabumi (Studi Kasus SD Muhammad Al-Unaizy Sukabumi) - Solihin MLF, Olih; Rachmawati, Ike (Jurnal Ilmiah Wahana Pendidikan, 2024)
Every Indonesian citizen, including children, has the right to education and benefit from science and technology, in order to improve their quality of life and for their welfare. Teaching and learning activities in schools are often tainted by actions that do not educate children. Bullying to unprofessional educators. In responding to these problems, the Sukabumi Regency Government made a policy by issuing Sukabumi Regent Regulation Number 17 of 2021 concerning Child-Friendly Schools. The author wants to examine how it is implemented in Muhammad Al-Unaizy Sukabumi Elementary School and what obstacles are faced during the implementation process. This research uses qualitative research methods with a sociological juridical approach, and with analytical descriptive specifications. Key data were collected by interviews, and literature studies. The collected data will be processed systematically and then analyzed qualitatively. Based on the results of the study, it is known that the implementation of the Child-Friendly School Policy at Muhammad Al-Unaizy Sukabumi Elementary School, is very ideal. Of the 38 component indicators that become the standard for the implementation of the Child Friendly School program, 34 of them are well fulfilled, while 4 components have not been fulfilled, namely the component of involving students in the formulation of activity plans and budgets, involving community institutions, involving business entities, and involving alumni.